Legal nature of the time limit for verification activities (Article 307 § 1 Criminal Procedure Code) (Ius Novum, 2020)
The article concerns the issue of verification activities which precede the institution of criminal proceedings and are aimed at determining legitimacy or admissibility of the criminal proceedings. The author focuses on the presentation of this problem from the viewpoint of the legal nature of the time limit for the said proceedings. The article adopts a dogmatic and legal method. The existing regulation has been analysed, its defects identified and amendments proposed. The general goal of the discussion is to postulate the development of solutions that would result from proper balancing of protected interests of the administration of justice and the necessity to respect human rights.
Keywords: verification activities; time limit; criminal proceedings; institution of criminal proceedings